Immediate Release Tablets of Valsartan and Efavirenz: Role of Concentration of Superdisintegrants - KESAVAN, K; RAO, UV; BINDU, K; RAJINIKANTH, PS; WANI, M; BALASUBRAMANIAM, J (Ars Pharmaceutica (Internet), 2008)
The objective of this study was to formulate directly compressible fast disintegrating tablets of poorly water solubledrugs with different extent of drug solubilities, like valsartan and efavirenz, as model drugs. Effect of varying concentrationsof different superdisintegrants such as crospovidone, croscarmellose sodium, and sodium starch glycolate ondisintegration time and in vitro drug dissolution was studied. The disintegration time of the best immediate release tabletformulation among those tested was observed to be 21.5±1.26 sec and 20.16±0.85 sec for valsartan and efavirenz tabletscontaining 20% of Crospovidone, respectively. Drug release (from both valsartan and Efavirenz tablets) was faster fromformulations containing crospovidone compared to the other formulation. The effect was more apparent in Efavirenz,which has lesser aqueous solubility than valsartan. It was observed that 20% crospovidone was required to achieve80% drug release from efavirenz tablets. Differential scanning calorimetric studies did not indicate any drug-excipientincompatibility. In conclusion, directly compressible fast disintegrating tablets of valsartan and efavirenz with shorterdisintegration times and high dissolution rate were obtained and crospovidone seemed to be a better disintegrant forboth valsartan and efavirenz, based on disintegration time and T80% values obtained.